ncry.net
ǰλãҳ >> 3(xһ|)(xʮ2)=xʮ4 >>

3(xһ|)(xʮ2)=xʮ4

3(xһ1)(x+2)=x+4:3(x+2x-x-2)=x+43x+3x-6=x+43x+2x-10=0=2-4x3x(-10)=124x=(-2124)/6=(-131)/3

3(xһ21131)(x+2)=x+4:52613(x+2x-x-2)=x+43x+3x-6=x+43x+2x-10=0=2-4x3x(-10)=1244102x=(-21653124)/6=(-131)/3

3/xһ2=a/xʮ4/x(xһ2):ͬx(x-2),3x=a(x-2)+43x-ax=-2a+4(3-a)x=-2a+4x=(4-2a)/(3-a)1. 4-2a=0a=2x=0,޽;2. (4-2a)/(3-a)=24-2a=6-2a.3. a=3޽.

3(x+2)=4(x+1)3x+6=4x+44x-3x=6-4x=2

3(xʮ2)=4(xʮ1) 3x+6=4x+4 (˷ 6-4=4x-3x ( 2=x x=2

4x=3(x-3)+2(x+3)-14x=3x-9+2x+6-13x+2x-4x=9-6+1x=4

5(xʮ13)=125 (xʮ13)=12.55=2.5 x=2.5-1.3=1.2 (2x16)x4=24 2x16=2.44 2x16=0.6 2x=0.6+16 2x=2.2 x=1.1 32xʮ08x=288 xĿԼӺ 4x=28.8 x=28.84=7.2 8xxʮ18=67 7x=67-18 7x=49 x=7 ͬʱԻͬһ,߲,ӼҲͬ.ǰĸһ,ַһ,мõȺ лл

(x+1)(x+2)(x+3)(x+4)+1= (x+1)(x+4)(x+2)(x+3) + 1= (x^2 + 5x +4)(x^2 + 5x + 6) + 1= (x^2 + 5x)^2 + 10(x^2 + 5x )+25=(x^2 + 5x + 5)^2֤.

ȷ,׷[xһ3][xʮ4]x+x-12ȷ,شûо!ллԱƼ!,ֻ!,롾ɴ𰸡,IJҴĶ,û

ֽʽ:(X+2)(X+3)+1/4=X^2+5X+25/2=(X+5/2)^2.

ĵ
վҳ | վͼ
All rights reserved Powered by www.ncry.net
copyright ©right 2010-2021
磬ַϵͷzhit325@qq.com